Inflammation, anxiety, and stress in bipolar disorder and borderline personality disorder: A narrative review. (August 2021) - Saccaro, L.F.; Schilliger, Z.; Dayer, A.; Perroud, N.; Piguet, C.
Highlights: BPD and BD are serious psychiatric disorders that share common features. Stress and inflammation have been implicated in their pathophysiology and etiology. Anxiety and emotional dysregulation are common symptoms associated to inflammation. Causal bidirectional relationships may exist between inflammation and these disorders. Unraveling these links may offer diagnostic, prognostic and therapeutic insights. Abstract: Bipolar disorder (BD) and borderline personality disorder (BPD) are serious and prevalent psychiatric diseases that share common phenomenological characteristics: symptoms (such as anxiety, affective lability or emotion dysregulation), neuroimaging features, risk factors and comorbidities. While several studies have focused on the link between stress and peripheral inflammation in other affective disorders such as anxiety or depression, fewer have explored this relationship in BD and BPD. This review reports on evidence showing an interplay between immune dysregulation, anxiety and stress, and how an altered acute neuroendocrine stress response may exist in these disorders. Moreover, we highlight limitations and confounding factors of these existing studies and discuss multidirectional hypotheses that either suggest inflammation or stress and anxiety as the primum movens in BD and BPD pathophysiology, or inflammation as a consequence of the pathophysiology of these diseases. Untangling these associations and implementing a transdiagnostic approach will have diagnostic, therapeutic and prognostic implications for BD and BPD patients.